The Effect Of Spinner Education On Students' Fiqh Learning Outcomes At The Madrasah Ibtidaiyah Level - Ahmad Afandi (proceedings.icesy, 2026)
Learning media play a strategic role in improving the quality of the learning process and learning outcomes, particularly in Islamic religious education at the Madrasah Ibtidaiyyah level. Limited variation in instructional media can lead to low student engagement and learning outcomes in Fiqih subjects. This study aims to analyze the effectiveness of Spinner Education as a game-based interactive learning medium in improving students’ Fiqih learning outcomes. The study employed a quantitative approach using a quasi-experimental design with pre-test and post-test applied to both the experimental and control groups. The research subjects consisted of 54 third-grade students of Madrasah Ibtidaiyyah Al-Ma’arif, divided equally into an experimental group (27 students) and a control group (27 students). Data were collected through learning achievement tests and analyzed using non-parametric statistical tests. The results indicate a significant difference in learning outcomes between students in the experimental group and those in the control group. These findings demonstrate that the use of Spinner Education is effective in improving Fiqih learning outcomes while simultaneously enhancing students' active participation and learning motivation. This study contributes to the enrichment of research on innovative learning media and supports the development of more interactive, contextual, and student-centered Fiqih learning at the Madrasah Ibtidaiyyah level.